"Evaluating the Effects of Submucosal Injection of Platelet Rich Plasma on Accelerating Orthodontic Tooth Movement During Leveling and Alignment Stage (Journal of Hama University, 2022)
To evaluate the effectiveness of injection of platelet rich plasma (PRP) in accelerating orthodontic tooth movement of crowded maxillary incisors.This two-arm, parallel-group, randomized controlled trial involved 26 patients with severe to extreme maxillary incisors irregularity according to Little’s irregularity index,indicating two first premolars extraction. Patients were randomly assigned to either the PRP group or the control group (13 each).Following premolars extraction, orthodontic treatment with fixedappliances was initiated for both groups. Immediately after insertion of the first archwire, patients in the PRP group receive the PRP injection , Alignmentprogress was evaluated on the study casts taken before inserting the first archwire (T0), after 1month of treatment commencement (T1), after 2 months (T2), and at the end of the leveling andalignment stage (T3). Results: A statistically significant difference was found between the two groups in the overall treatment time (P > .001